2015
DOI: 10.3741/jkwra.2015.48.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Meteorological Drought and Hydrological Drought Index

Abstract: In this study, meteorological drought indices were examined to simulate hydrological drought. SPI (Standardized Precipitation Index) and SPEI (Standardized Precipitation Evapotranspiration Index) was applied to represent meteorological drought. Further, in order to evaluate the hydrological drought, monthly total inflow and SDI (Streamflow Drought Index) was computed. Finally, the correlation between meteorological and hydrological drought indices were analyzed. As a results, in monthly correlation comparison,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…각각의 가뭄은 목적에 따라 여러 지수들로 분석되고 있다. 가뭄에 따른 피해 에 대응하고 관리하기 위하여 전 세계적으로 SPI (Standardized Precipitation Index; Mckee et al, 1993), SPEI (Standardized Precipitation Evapotranspiration Index; Vicente-Serrano et al, 2010), SDI (Streamflow Drought Index; Nalbantis, 2008), PDSI (Palmer Drough Severity Index;Palmer, 1965), SWSI (Surface Water Supply Index; Shafer and Dezman, 1982), Streamflow drought severity-durationfrequency (SDF) curve (Sung and Chung, 2014) Pisani et al, 1998;Heim, 2002;Keyantash and Dracup, 2002;Lee, et al, 2015 (Morid et al, 2006;Smakhtin and Hughes, 2007;Banimahd and Khalili, 2013…”
Section: 서 론mentioning
confidence: 99%
“…각각의 가뭄은 목적에 따라 여러 지수들로 분석되고 있다. 가뭄에 따른 피해 에 대응하고 관리하기 위하여 전 세계적으로 SPI (Standardized Precipitation Index; Mckee et al, 1993), SPEI (Standardized Precipitation Evapotranspiration Index; Vicente-Serrano et al, 2010), SDI (Streamflow Drought Index; Nalbantis, 2008), PDSI (Palmer Drough Severity Index;Palmer, 1965), SWSI (Surface Water Supply Index; Shafer and Dezman, 1982), Streamflow drought severity-durationfrequency (SDF) curve (Sung and Chung, 2014) Pisani et al, 1998;Heim, 2002;Keyantash and Dracup, 2002;Lee, et al, 2015 (Morid et al, 2006;Smakhtin and Hughes, 2007;Banimahd and Khalili, 2013…”
Section: 서 론mentioning
confidence: 99%
“…Although several research found no association between meteorological and hydrological droughts, numerous investigations have shown a link, for example in Korea. (Lee et al 2015), and in the West Sterea Hellas Water District in Greece (Nalbantis and Tsakiris 2009). Moreover, a linear function of SPI was discovered to predict SDI with sufficient accuracy to characterize drought severity (Nalbantis and Tsakiris 2009).…”
Section: Introductionmentioning
confidence: 99%
“…가뭄 모니터링 방법, 가뭄의 크기, 지속기간, 강도 등 가뭄 정량화와 특성을 판단하는 기준은 연구자, 재난 관리담당자 및 기관마다 다를 수 있다. 특히 가뭄을 정량적인 값으로 산정하고 평가하는 것은 다양한 수문기상학적 변 수와 조합방식에 따라 달라진다 (Tsakiris et al, 2007;Lee et al, 2015).…”
Section: Introductionunclassified
“…최근에는 단일 가뭄지수의 활용에 의존하기 보다, 여러 가뭄지수 간의 특징과 장단점을 상호보완한 연구를 권하고 있다 (Lee et al, 2015;Nam et al, 2017) Chen and Sun, 2015; Kingston et al, 2015;Potopova et al, 2016;Zhao et al, 2017).…”
Section: Introductionunclassified